Finland : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
The economic restructuring and expansion after the crisis reflected a combination of private sector initiative, solid macroeconomic management, including the shift from large deficits to significant surpluses of the general government, and structural reforms. High unemployment is one indication that structural rigidities continue to hamper Finland's output potential. In the face of high unemployment and rapid population aging, the discussions focused on supporting medium-term growth while securing long-term fiscal sustainability. Reflecting concerns about slowing growth, front-loaded expenditure increases, and tax cuts were at the center of the fiscal policy debate.